2015
DOI: 10.1097/01.aoa.0000469490.12751.44
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Abnormalities in Pregnancy-associated Hypertension

Abstract: in blood pressure or urine output. During the period of 12 to 24 hours after start of treatment, the mean urine output for the 12-hour group was 128.3 mL/h and 159.8 mL/h for the 24-hour group (P = 0.008). Episodes of very high blood pressure did not differ between the groups. In the 12-hour group, 3 women had the therapy extended, but in the 24 hours, no patient required extension of her treatment. No patient stopped therapy because of adverse effects of the drug and none had to restart treatment after suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Additionally, laboratory abnormalities were associated with an increased risk of abruption, neonatal intensive care unit admission, and neonatal composite outcome. 15 Our data are similar, citing a laboratory abnormality rate of 6.3% among all PE groups, although our cohort excludes gestational hypertension and did not stratify for low-risk characteristics. Our study adds to the literature by evaluating the timing of laboratory assessment and suggesting an optimal frequency of evaluation, where previous guidelines were based predominantly on expert opinion.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, laboratory abnormalities were associated with an increased risk of abruption, neonatal intensive care unit admission, and neonatal composite outcome. 15 Our data are similar, citing a laboratory abnormality rate of 6.3% among all PE groups, although our cohort excludes gestational hypertension and did not stratify for low-risk characteristics. Our study adds to the literature by evaluating the timing of laboratory assessment and suggesting an optimal frequency of evaluation, where previous guidelines were based predominantly on expert opinion.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have identified laboratory abnormalities as harbingers of HELLP syndrome as well as poor perinatal outcomes, 15 16 17 and early detection and treatment of laboratory abnormalities may have the potential to impact maternal and fetal outcomes. As PE is responsible for significant monetary expenditure in the health care system especially in cases of preterm birth, 18 with estimates of United States spending as high as $2.18 billion within the first 12 months of PE-related delivery, 19 developing cost-conscious protocols aimed at improving maternal and fetal outcomes is imperative.…”
mentioning
confidence: 99%
“…The adverse effect was more obvious with the increase of severity of this disease. The study of Cantu et al [15] found that laboratory abnormalities increased with severity of hypertension: mild hypertension alone (4.9%), severe hypertension alone (8.9%), and mild or severe hypertension with clinical signs of end-organ dysfunction (12.2%) (p < 0.001).…”
Section: Discussionmentioning
confidence: 97%